2008
DOI: 10.1016/j.vacuum.2008.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal treatments on the structure of MoNxOy thin films

Abstract: MoN x O y films were deposited on steel substrates by dc reactive magnetron sputtering. The depositions were carried out from a pure molybdenum target, varying the flow rate of reactive gases. X-ray diffraction (XRD) results revealed the occurrence of cubic MoN x and hexagonal (d-MoN) phases for the films with high nitrogen flow rates. The increase of oxygen content induces the decrease of the grain size of the molybdenum nitride crystallites. The thermal stability of a set of samples was studied in vacuum, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
4
6
0
Order By: Relevance
“…It is similar to the for Mo 2 N coating presented in our previous paper [47]. Cunha et al [45] calculate the grain size for (111) and (200) planes as about 11 nm and 6 nm, respectively.…”
Section: Xrdsupporting
confidence: 88%
See 1 more Smart Citation
“…It is similar to the for Mo 2 N coating presented in our previous paper [47]. Cunha et al [45] calculate the grain size for (111) and (200) planes as about 11 nm and 6 nm, respectively.…”
Section: Xrdsupporting
confidence: 88%
“…The occurrence of compressive stresses is typical for PVD coatings [44]. A similar level of stress (−1.5 GPa) was determined by Cuhna et al [45] and a level two times higher was reported by Sarioglu et al [46]. The stress in the coating consists of a thermal stress associated with the different thermal expansion coefficients Mo 2 N (6.2 × 10 −6 K −1 ), CrN (2.3 × 10 −6 K −1 ) of layers and the steel substrate (11 × 10 −6 K −1 ) and the stress caused by ion bombardment of the surface layer [46].…”
Section: General Characterisation Of Deposited Samplessupporting
confidence: 82%
“…We should note that that the characteristics of Mo-Si-B-N coatings obtained in optimal regimes surpass those of the known Mo-Si-N and Mo-B-N sys tems, which have H = 25 GPa [10] and H = 10-20 GPa [36], respectively.…”
Section: Resultsmentioning
confidence: 77%
“…One of the disadvantages that have limited the application of MoN coatings is their intense oxidation in the temperature range of 350-400°C accompanied by the formation of volatile oxide MoO 3 [9]. More over, low thermal stability of MoN coatings associated with phase transition γ MoN → δ MoN and intense crystallite growth at 700-800°C should be noted [10].…”
Section: Introductionmentioning
confidence: 99%
“…The industrial importance of these materials keeps growing rapidly, not only in the well-established applications based on the strength and refractory nature of these materials such as cutting tools and abrasives, but also in new and promising fields such as electronics, optoelectronics and medical device applications [3e9]. More recently and using the idea of tailoring the film's properties between those of metal nitrides, MeN x , and those of the correspondent insulating oxides, MeO y , a new class of materials gained more importance in several technological applications: the metal oxynitrides MeN x O y , where Me can be Al [10e13], Cr [14], Ta [15], Nb [16], Zr [17] [18], Mo [19], Ti [20,21], among others. These ternary materials allow, in principle, merging the benefits of the basic characteristics of both metal nitrides and oxides.…”
Section: Introductionmentioning
confidence: 99%